Keterampilan Sosial Pustakawan dalam Menghadapi Masyarakat Informasi di Era Information Overload - Maydani Nur Majidah; Anis Masruri (Perpustakaan Universitas Gadjah Mada, 2025)
The phenomenon of information overload in the digital era places librarians as information facilitators who must have superior social skills.This research aims to explore the role of librarians' social skills in facing the information society and the challenges that come with it. Social skills such as interpersonal communication, empathy, cooperation, and emotional management are important foundations for creating responsive library services. The research method uses a literature approach by analyzing related literature. The results showed that librarians are not only information providers but also as agents of change. Agent of change that supports information literacy and the wise use of information. In facing the challenges of information overload, librarians must identify community’s information needs, utilize digital technology, and develop the community’s information needs, utilize digital technology, and develop relevant innovative programs. In addition, the development of social skills such as empathy, lobbying, and negotiation skills is needed to build good relationships with the community and stakeholders. This research confirms the importance of librarians' social skills as a core element in library services. The results of this study are expected to provide recommendations for library institutions to design more effective social skills training.